ChemInform Abstract: RhIII‐Catalyzed Redox‐Neutral C—H Activation of Pyrazolones: An Economical Approach for the Synthesis of N‐Substituted Indoles. Issue 23 (June 2015) - Fan, Zhoulong; Song, Shanshan; Li, Wei; Geng, Kaijun; Xu, Youjun; Miao, Ze‐Hong; Zhang, Ao
Abstract The reaction tolerates 3‐, 4‐ and 3, 4‐substitutions in the aromatic groups in the pyrazolones, but no 2‐substituted or heteroaromatic groups.